Effectiveness of Herbal Treatment on Otitis Media: A Literature Review - Desi Waluya; Sri Kurnia Dewi; Siti Umaemah; Aneu Rahmawati; Rani Rahmawati (Jurnal Kesehatan, 2025)
Introduction: Otitis media is inflammation of part or all of the middle ear mucosa, Eustachian tube, mastoid antrum, and mastoid cells. Treatment that can be given to otitis media is by using antibiotics. However, herbal medicine can also be used. Method: This research is secondary research using the literature review method. Results: The use of herbal ingredients such as ginger, tebel-tebel (Hoya carnosa), and ethanol extract of kaffir lime (Citrus hystrix) turned out to be effective and has strong antifungal and/or antibacterial properties. However, binahong (Anredera cordifolia) leaf extract was not effective against bacteria, the antibacterial activity showed a weak inhibitory response, with an average inhibitory area diameter (DDH) of 0.00 mm. Conclusion: Overall, several herbal medicines showed great potential as alternatives to antibiotics, except for binahong leaf extract which was less effective. Further studies are needed to strengthen the results and clinical applications.